Extraction of a tooth with apical periodontitis in an adult with cherubism. Issue 3 (May 2020) - Kutsuna, Tomohiko; Satake, Mami; Okumura, Kenya; Kitamura, Tetsuya; Tomeoku, Akira; Arai, Naoya
Abstract: Cherubism is a hereditary disease that generally presents during childhood and causes bilateral symmetrical enlargement of the jaws. It is a self-limiting disease that spontaneously remits or regresses after puberty, in most cases. Owing to the rarity of the disease, there have been few reports about patients with cherubism, who underwent tooth extraction due to dental caries and apical periodontitis. We present the case of an adult patient with cherubism, who underwent dental extraction due to chronic apical periodontitis, at a bony site that was involved with a lesion in the affected jaw. A 19-year-old woman with cherubism, exhibiting severe bilateral expansion of the lower jaw, had a decayed second molar present in a lesion of her affected mandible. Although she had reached adulthood, it was unclear if active growth of the lesion had been arrested. On removal, the tooth showed osseous ankyloses and required root separation. Postoperative healing was normal and without complications, such as wound infection and regrowth of the lesion. Histologically, the periapical lesion comprised granulation tissue accompanied by inflammatory cell infiltration and blood capillaries. The alveolar septum consisted of lamellar trabecular bone surrounded by fibrous tissue. Typical histological findings of cherubism, such as multinucleated giant cells and newly formed bone, were absent both within and near the extraction site. A case of cherubism with uneventful dental extraction, necessitated by chronic infection, has not been reported to date.